The revised Permian genus Dagmarita Reitlinger, 1965 (Dagmaritinae, Foraminifera) and its phylogenetic relationships. (March 2020) - Gennari, Valerio; Rettori, Roberto
Abstract: Among Permian smaller foraminifers, the genus Dagmarita is one of the most studied due to its worldwide distribution. The detailed study of the Zal (NW Iran) and Abadeh (Central Iran) stratigraphic sections led to redescription of the genus Dagmarita and its taxonomic composition. In Dagmarita, a peculiar generic morphological character, represented by a secondary valvular projection, has been detected for the first time among globivalvulinid foraminifers. The phylogeny of Dagmarita, and in particular its ancestor Sengoerina, is discussed and the new species, D . ghorbanii n. sp. and D . zalensis n. sp., are introduced. Analogies and differences among all the species belonging to Dagmarita are highlighted and morphological features of the new taxa are shown in 3D reconstructions, useful for understanding differently oriented sections of the specimens in thin section. UUID: http://zoobank.org/3d8eb14c-7757-4cbd-877c-4bacd2d156da